Project 110 - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
A second experiment was conducted with fall pigs in the dry lot. Two lots of pigs were used. One lot received the RQ-20 in the protein mixture at the rate of 3 pounds to 600 pounds of supplement. The mixture was self-fed with the shelled corn and was composed of 4 parts tankage, 4 parts soybean meal, 1 part alfalfa meal, and 1 part linseed meal in the dry lot.
Keywords: Swine; Gain; Protein